Model Sistem Informasi Penjualan Pada Apotek Berbasis Web - Indah Rizza Ummami; Izzatul Umami; M Gugus Azhari (STMIK Banjarbaru, 2022)
The practice of recording incoming and outgoing goods at An-Nur Pharmacy, which is still done manually in the book of buying and selling drugs, causes processing errors by service personnel, as well as inefficient processing times, especially when there is a high volume of transactions. The purpose of this study is to build a web-based information system model that facilitates drug data processing and provides comprehensive data on the types of drugs provided in pharmacies. This study uses the System Development Life Cycle (SDLC) approach, which uses the PHP programming language and MySQL database to build the system. The Web-based system integrates system administrators, service employees and business owners in the management of buying and selling of products (medicines). The main functional features in the form of managing goods and supplies, managing suppliers, managing purchases and sales, and managing online management reporting, were tested using the Blackbox Testing technique. The test results show that all program functions that have been identified in the needs analysis phase have been fulfilled validly.Keywords: Sales and Purchases; Medicines; Application Program; System Development Life Cycle; Black box testing. Abstrak. Praktik pencatatan barang masuk dan keluar pada Apotek An-Nur yang masih dilakukan secara manual pada buku pencatatan pembelian dan penjualan obat, menyebabkan terjadinya kesalah proses oleh petugas pelayanan, serta waktu proses yang tidak efisien, terlebih ketika sedang tingginya volume transaksi yang terjadi. Tujuan dari penelitian ini adalah untuk membangun model sistem informasi berbasis web yang memfasilitasi pengolahan data obat dan memberikan data yang komprehensif tentang jenis obat yang disediakan di apotek. Penelitian ini menggunakan pendekatan System Development Life Cycle (SDLC), yang menggunakan bahasa pemrograman PHP dan database MySQL dalam membangun sistem. Sistem berbasis Web mengintegrasikan pihak Administrator sistem, Pegawai Pelayanan, dan Pemilik Usaha dalam manajemen pembelian dan penjualan produk (obat-obatan). Fitur-fitur fungsional utama berupa kelola barang dan persediaan, kelola supplier, kelola pembelian dan penjualan, serta kelola pelaporan manajemen secara online, diuji menggunakan teknik Pengujian Blackbox. Hasil pengujian menunjukkan seluruh fungsi-fungsi program yang telah diidentifikasi pada fase analisis kebutuhan telah dipenuhi secara valid.